Physical-biological coupling in the Amundsen Sea, Antarctica: Influence of physical factors on phytoplankton community structure and biomass. (November 2016) - Lee, Youngju; Yang, Eun Jin; Park, Jisoo; Jung, Jinyoung; Kim, Tae Wan; Lee, SangHoon
Abstract: To understand the spatial distribution of phytoplankton communities in various habitats in the Amundsen Sea, western Antarctica, a field survey was conducted at 15 stations during the austral summer, from December 2013 to January 2014. Water samples were analyzed by microscopy. We found high phytoplankton abundance and biomass in the Amundsen Sea polynya (ASP). Their strong positive correlation with water temperature suggests that phytoplankton biomass accumulated in the surface layer of the stratified polynya. In the ASP, the predominant phytoplankton species was Phaeocystis antarctica, while diatoms formed a major group in the sea ice zone, especially Fragilariopsis spp., Chaetoceros spp., and Proboscia spp. Although this large diatom abundance sharply decreased just off the marginal sea ice zone, weakly silicified diatoms, due to their high buoyancy, were distributed at almost all stations on the continental shelf. Dictyocha speculum appeared to favor the area between the marginal sea ice zone and the ASP in contrast to cryptophytes and picophytoplankton, whose abundance was higher in the area between the continental shelf and the open ocean of Amundsen Sea. Several environmental factors were found to affect the spatial variation of phytoplankton species, but the community structure appeared to be controlled mainly by the seawater density related to sea-ice melting and water circulation in the Amundsen Sea. Highlights: We analyzed the phytoplankton community in the Amundsen Sea, Antarctica, by microscopy. Phaeocystis antarctica and diatoms were major group during the austral summer. The spatial distribution of diatoms differed according to their buoyancy. The phytoplankton community structure seemed to be influenced by water density and sea ice melt.